The Effectiveness of Nano Indian Costus Root Extract on Some Types of (Candida) Isolated from the Respiratory System - Baida’a Hussein Ali; Mithaq Sattar Aboud (International Journal of Medical Toxicology and Legal Medicine, 2024)
Many methods have historically been used to synthesize nanoparticles (NPs). However, many of these methods have proven to be expensive, producing toxic by-products and necessitating measures to mitigate chemical and physical pollution. Thus, adoption of green nanoparticle synthesis using plant extracts has emerged as sustainable alternative in the field of nanotechnology Indian premium root extract for ZnO nanoparticle synthesis. Characterization of nan particles, including UV-Vis visible spectroscopy, scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FT-IR) and X-ray diffraction (XRD), demonstrates the effectiveness of use of Indian costus root extract in environmentally friendly synthesis of ZnO nanoparticles and efficacy on some Candida spp types, C. albicansC. C.tropicalis, C.glbrata, and that nanotechnology has far-reaching implications across various scientific and industrial fields.